Organocatalytic Enantioselective aza-Michael Reactions - Reyes, Efraim; Fernandez, Maitane; Uria, Uxue; L. Vicario, Jose; Badia, Dolores; Carrillo, Luisa (Current Organic Chemistry, 2012)
The catalytic enantioselective aza-Michael reaction is an important transformation in organic chemistry, which has been used for the synthesis of a significant amount of nitrogen-containing products for many research areas in chemistry. In this review, we summarize the literature dealing with catalytic enantioselective versions of this transformation, where a small chiral organic molecule which does not contain metal atoms within its structure (the organocatalyst) is employed for promoting the reaction and also for controlling its stereochemical outcome. Several examples highlighting the successful application of this methodology will also be presented, emphasized by the description of the enantioselective total synthesis of several natural products and therapeutics.
Keywords: proline-based derivatives